2022
DOI: 10.3390/membranes12111066
|View full text |Cite
|
Sign up to set email alerts
|

Development of Ultrafiltration Kaolin Membranes over Sand and Zeolite Supports for the Treatment of Electroplating Wastewater

Abstract: A high cost of high-purity materials is one of the major factors that limit the application of ceramic membranes. Consequently, the focus was shifted to using natural and abundant low-cost materials such as zeolite, clay, sand, etc. as alternatives to well-known pure metallic oxides, such as alumina, silica, zirconia and titania, which are usually used for ceramic membrane fabrication. As a contribution to this area, the development and characterization of new low-cost ultrafiltration (UF) membranes made from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 55 publications
(80 reference statements)
2
3
0
Order By: Relevance
“…Contrary to the mechanical strength, as shown in Figure 7, the porosity decreased with an increasing in sintering temperature. This result is consistent with the trends found in the literature [38,44], indicating that an increase in the sintering temperature promotes particle fusion and compaction, thereby reducing the overall porosity of the sepiolite membrane. This densification leads to a decrease in the volume of void spaces within the material, resulting in a more compact and homogeneous structure which reduces the porosity.…”
Section: Mechanical Strength and Porositysupporting
confidence: 93%
See 1 more Smart Citation
“…Contrary to the mechanical strength, as shown in Figure 7, the porosity decreased with an increasing in sintering temperature. This result is consistent with the trends found in the literature [38,44], indicating that an increase in the sintering temperature promotes particle fusion and compaction, thereby reducing the overall porosity of the sepiolite membrane. This densification leads to a decrease in the volume of void spaces within the material, resulting in a more compact and homogeneous structure which reduces the porosity.…”
Section: Mechanical Strength and Porositysupporting
confidence: 93%
“…A higher FDR value indicates a greater decrease in the permeate flux, showing a higher susceptibility to fouling, while a higher FRR value indicates better recovery of the permeate flux after cleaning, demonstrating the membrane's ability to regain its initial performance. FDR and FRR may be calculated and compared to determine the UF membrane's capacity to resist fouling [38].…”
Section: Evaluation Of the Fouling Resistance Capacitiesmentioning
confidence: 99%
“…For the M S50-Z50 membrane, R 2 is relatively low (<0.900); therefore, it can be deduced that the Hermia model did not correlate with the experimental data. The suggested pore-blocking model for M S10-Z90 and the retained result for M S50-Z50 were similar to the Kaolin membranes prepared in our laboratory [38]. Additionally, Beqqour et al [33] proved standard pore-blocking using a flat membrane made from natural pozzolan and micronized phosphate like our M S30-Z70 membrane.…”
Section: Separation Mechanisms and Fouling Studysupporting
confidence: 80%
“…In addition, P and S peaks are related to smectite composition. Small carbon-related peaks were detected, which may be due to impurities [38].…”
Section: Morphology and Pore Size Analysismentioning
confidence: 99%
“…Several studies have employed ceramic membranes in wastewater treatment and the search for low-cost and environmentally friendly starting materials has continued to engender research interests. Therefore, solid wastes and readily available materials rich in Al 2 O 3 and SiO 2 such as coal fly ash, natural clay, kaolin and sand can be used as starting material for ceramic membranes [ [40] , [41] , [42] , [43] ]. Studies by Hossain and Roy [ 44 ] and Sawunyama et al [ 45 ] reported that coal fly ash and bentonite clay had significant amounts of Al 2 O 3 and SiO 2 which can make them good candidates for ceramic membranes raw materials.…”
Section: Introductionmentioning
confidence: 99%